Migrant well-being after leaving transition economies - Milena Nikolova (IZA World of Labor, 2015)
Most comparative research suggests that immigrants from post-socialist countries earn less than natives, work in jobs for which they are overqualified, and may experience unhappiness compared with natives, other immigrants, and non-migrants. In contrast, one study presents causal evidence which shows that moving from transition economies to live in the West increases the incomes, life satisfaction, and freedom perceptions of those who move. Credibly assessing whether leaving transition economies improves movers' quality of life remains a challenging empirical question.
Keywords: F22; I31; O15; P30; 330; transition countries; well-being; migration